Mental health in the workplace in the age of artificial intelligence - Rodríguez Escanciano, Susana (LABOS Revista de Derecho del Trabajo y Protección Social, 2026)
It is an incontrovertible fact, statistically proven, that new smart technologies contribute to a global decrease in accident rates, improving the well-being of workers. However, their dark side cannot be ignored either, as they do not eliminate harmful substances entirely, adding to traditional risks other emerging hazards capable of crossing the thin and vulnerable line of mental health, so severely impacted by the pandemic and so threatened in the current production environment. This worrying reality compels us to design appropriate legal responses that cannot be limited to providing mere compensatory protection, but rather require a commitment to an effective preventative policy in the workplace.